Implementasi Teknologi Augmented Reality dalam Sains berbasis Android dengan Kartu Interaktif - Aminudin, Nur; Mutmainah, Mutmainah; A, Afnan Zalfa Salsabila (Jurnal Teknologi Terpadu, 2024)
Significant changes in education have resulted from the advancement of information technology, particularly in the area of abstract science teaching. Android-based Augmented Reality (AR) technology using interactive cards as educational materials is one possible breakthrough. Through interactive visualizations that enable in-depth subject analysis, this project seeks to increase student comprehension and engagement. The ASSURE model served as the basis for the research and development (R&D) methodology used in the study. Learning needs and technology are integrated in this paradigm, which consists of the following steps: Analyze Learners, State Objectives, Select Media and Materials, Utilize Media and Materials, Require Learner Participation, and Evaluate and Revise. Data were collected during a four-week observation period using pretest and posttest tests. An n-gain of 0.71 (high category) in the experimental class and 0.47 (moderate category) in the control class indicated a substantial increase, according to paired sample t-test analysis. The primary distinction was that the control class had less access to AR devices. The findings demonstrated that AR increased student comprehension and involvement. However, obstacles included infrastructural needs and sample limits. To investigate AR's efficacy on a broader scale and its influence on long-term learning results, more research is advised.